Temperature-sensitive mutants of influenza WSN virus defective in virus-specific RNA synthesis. - Krug, R M (1975)
Influenza WSN virus temperature-sensitive (ts) mutants were examined for defects in viral complementary RNA (cRNA) synthesis. The synthesis of viral cRNA was determined by hybridizing RNA from infected cells to radiolabeled virion RNA of known specific activity. Mutants in complementation groups I and III synthesized little, or no, cRNA at the nonpermissive temperature (39.5 C). When cells infected by these mutants were incubated for 5 h at the permissive temperature (33 C) and were then shifted to 39.5 C, net synthesis of cRNA ceased. This strongly suggests that mutants in these two complementation groups possess a ts defect in the transciptase complex. Mutants in group II and group V synthesize reduced amounts of cRNA at 39.5 C. In contrast to the group I and group III mutants, cRNA synthesis in cells infected by a group II or a group V mutant continues after a shift-up. This indicated that these mutants do not possess a ts transcriptase complex and that these mutants are most probably defective in some step in the amplification of cRNA synthesis. As will be discussed, the most likely defect in these mutants is in the synthesis of virion-type RNA. These results suggest that there are two influenza viral gene functions required for transcription and most likely two additional gene functions required for RNA replication.